Vulnerability to radicalisation in a general population: a psychometric network approach - Clemmow, Caitlin (Psychology, crime & law, 2023)
A public health approach to countering the threat from extremism aims to manage vulnerability before behaviour escalates to require involvement from the criminal justice system. Fundamental to applying a public health approach is understanding how risk (and protective) factors can be modified, in other words, the functional roles of these factors. To unpack the functional roles of risk factors, a more dynamic approach to modelling the complex relationships between factors is needed. In the present study we surveyed a representative sample of the UK general population (n = 1500) where participants self-reported risk factors and indicators for vulnerability to radicalisation. Operationalising analytical guidance from a Risk Analysis Framework (RAF), we applied psychometric network modelling to visualise the relationships among risk factors relating to individual-level propensities, situational influences, and exposure to extremism-enabling environments. We present our results as a series of network graphs and discuss (a) how risk factors ‘cluster’ or ‘co-occur’, (b) the most influential risk factors which may be important for intervention and prevention, and (c) ‘risk pathways’ which suggest potential putative risk and/or protective factors. We present our findings as evidence for a public health approach to countering the threat from extremism.